2005
DOI: 10.1016/j.acra.2005.01.012
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Volumetric MRI Using Parallel Imaging With Order-of-Magnitude Accelerations and a 32-Element RF Coil Array

Abstract: Rationale and Objectives-Many clinical applications of Magnetic Resonance Imaging are constrained by basic limits on imaging speed. Parallel MRI relaxes these limits by using the sensitivity patterns of arrays of radiofrequency receiver coils to encode spatial information in a manner complementary to traditional encoding with magnetic field gradients. Until now, parallel MRI has been used to achieve modest improvements in imaging speed; order-of-magnitude improvements have been elusive given fundamental losses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
44
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 67 publications
(45 citation statements)
references
References 27 publications
0
44
0
1
Order By: Relevance
“…This excess degradation is characterized by a geometry factor, also known as the g-factor. 43 It is possible that a similar SNR-degrading factor also exists in CS MRI, a topic that warrants attention. However, SNR comparisons are only Figure 9.…”
Section: Waveletmentioning
confidence: 99%
“…This excess degradation is characterized by a geometry factor, also known as the g-factor. 43 It is possible that a similar SNR-degrading factor also exists in CS MRI, a topic that warrants attention. However, SNR comparisons are only Figure 9.…”
Section: Waveletmentioning
confidence: 99%
“…Although image quality was rated equally high for the two contrast agents at both field strengths, the evidently increased CNR caused by P1152 may offer potential to improve the diagnostic performance of CE-MRA. Advanced imaging applications which take advantage of high-acceleration parallel acquisition techniques (10,11) are associated with a considerable decrease of the signal intensity (12). This drawback might be partially counterbalanced by the use of contrast agents with higher relaxivities.…”
Section: Discussionmentioning
confidence: 99%
“…A 32-channel acquisition system was constructed using four sets of GE EXCITE II system electronics (GE Healthcare Technologies, Waukesha, WI, USA) in a master-slave arrangement (24,25). Each set consisted of eight channels that included analog-to-digital converters, a digital data pipeline, and a scanner console.…”
Section: Hardwarementioning
confidence: 99%
“…Third, a sufficient number of receivers allows the use of multidimensional RF coil array arrangements that are capable of multidimensional accelerations, which will serve to reduce the noise amplification that is inherent to parallel imaging and hence preserve SNR as compared to 1D accelerations (22,23). Furthermore, recent studies have shown that large 3D volumetric acquisitions that can benefit the most from multidimensional acceleration also serve to recover SNR via noise averaging (24,25).…”
mentioning
confidence: 99%